2020
DOI: 10.1039/d0ra04070c
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid derivatives are potent inhibitors against porcine reproductive and respiratory syndrome virus

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most devastating viral pathogens of swine and has a substantial economic impact on the global pork industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Atractylodinol and ethoxysanguinarine were reported to have anti-PRRSV activity with an inhibitory concentration of 50% (IC 50 ) of 7.9 and 39.4 μM, respectively ( 58 ). 3-O-b-chacotriosyl ursolic acid and its ester analogs exhibited potent anti-PRRSV activity in vitro with minimal cytotoxicity ( 59 ). Nevertheless, there is still a long time before these compounds are further developed into approved drugs since novel drug development is of high cost and risk.…”
Section: Discussionmentioning
confidence: 99%
“…Atractylodinol and ethoxysanguinarine were reported to have anti-PRRSV activity with an inhibitory concentration of 50% (IC 50 ) of 7.9 and 39.4 μM, respectively ( 58 ). 3-O-b-chacotriosyl ursolic acid and its ester analogs exhibited potent anti-PRRSV activity in vitro with minimal cytotoxicity ( 59 ). Nevertheless, there is still a long time before these compounds are further developed into approved drugs since novel drug development is of high cost and risk.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable structure of UA over OA probably contributes to the better antimicrobial activity of UA. A negative effect on the antimicrobial activity was confirmed when the methyl group was replaced by a -CH 2 OH, a -CHO, or a -COOH group [25], indicating that the methyl group appears to be necessary and sufficient for antibacterial activity. This further proves our deduction that a methyl group may be an important group that plays an antibacterial role.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study revealed that UA reduces expression of human papilloma virus À18 (HPV-18) E6/E7 genes in HeLa cells; however expression of p53 did not change [25]. Similarly, a recent study by Chen et al, revealed that UA derivatives are effective against porcine reproductive and respiratory syndrome virus through direct inactivation of viral virion and replication [26].…”
Section: Antiviral Effects Of Ursolic Acidmentioning
confidence: 97%